180° congenital penile torsion with distal hypospadias mistaken for an epispadias: Optimal outcome with tubularized incised plate urethroplasty and dartos flap rotation. Issue 6 (7th September 2019) - Cassell, Ayun; Jalloh, Mohamed; Mbodji, Mouhamadou M; Ndoye, Medina; Labou, Issa; Niang, Lamine; Diallo, Yoro; Diallo, Abdourahmane; Gueye, Serigne M
Abstract : Introduction: Severe penile torsion of 180° associated with hypospadias is a rare entity. Knowledge of penile anatomy and pathology are necessary as the diagnosis could be missed. Case presentation: We report a case of severe 180° penile torsion with distal hypospadias that was mistaken for an epispadias which was corrected with surgery. Conclusion: Tubularized incised plate urethroplasty and dartos flap rotation provided satisfactory result for this association.